Niobium Nitride Nb4N5 as a New High‐Performance Electrode Material for Supercapacitors. Issue 12 (15th July 2015) - Cui, Houlei; Zhu, Guilian; Liu, Xiangye; Liu, Fengxin; Xie, Yian; Yang, Chongyin; Lin, Tianquan; Gu, Hui; Huang, Fuqiang
Abstract : Supercapacitors suffer either from low capacitance for carbon or derivate electrodes or from poor electrical conductivity and electrochemical stability for metal oxide or conducting polymer electrodes. Transition metal nitrides possess fair electrical conductivity but superior chemical stability, which may be desirable candidates for supercapacitors. Herein, niobium nitride, Nb4 N5, is explored to be an excellent capacitive material for the first time. An areal capacitance of 225.8 mF cm −2, with a reasonable rate capability (60.8% retention from 0.5 to 10 mA cm −2 ) and cycling stability (70.9% retention after 2000 cycles), is achieved in Nb4 N5 nanochannels electrode with prominent electrical conductivity and electrochemical activity. Faradaic pseudocapacitance is confirmed by the mechanistic studies, deriving from the proton incorporation/chemisorption reaction owing to the copious +5 valence Nb ions in Nb4 N5 . Moreover, this Nb4 N5 nanochannels electrode with an ultrathin carbon coating exhibits nearly 100% capacitance retention after 2000 CV cycles, which is an excellent cycling stability for metal nitride materials. Thus, the Nb4 N5 nanochannels are qualified for a candidate for supercapacitors and other energy storage applications. Abstract : Highly ordered Nb4 N5 nanochannels are successfully prepared by anodizing of Nb foil and subsequent annealing in ammonia atmosphere, and their electrochemical performance as supercapacitor electrodes is studied for the first time. An areal capacitance of 225.8 mF cm −2 is achieved, with reasonable rate capability and cycling stability. The electrochemical stability is further improved with a thin carbon coating.